Pengaruh Memakai Masker Terhadap Karakter Disiplin Anak Kelompok B di Kelompok Bermain Bintang Kecil Kabupaten Banyuasin - Rut Suprapti; Taty Fauzi; Dessi Andriani (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the effect of wearing a mask on the discipline character of children in group B in the Bintang Kecil Play Group. The research sample was 20 children. The research method uses the One Group Pretest-Posttest Design experimental method. Collecting data using tests and analyzed by t test. To prove the usability of the test instrument, it was carried out through normality and homogeneity tests, then tested the effectiveness of the intervention test. The results of the calculation of the average value of 54.626 means that the use of wearing masks has an influence on the formation of the discipline character of group B children in the Bintang Kecil Play Group, Banyuasin Regency.